Coumarins as Powerful Photosensitizers for the Cationic Polymerization of Epoxy-Silicones under Near-UV and Visible Light and Applications for 3D Printing Technology - Mira Abdallah; Akram Hijazi; Frédéric Dumur; Jacques Lalevée (Molecules, 2020)
In this study, eight coumarins (coumarins 1–8) are proposed as near-UV and blue light sensitive photoinitiators/photosensitizers for the cationic polymerization (CP) of epoxysilicones when combined with 4-isopropyl-4’-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (IOD). Among these coumarins, four of them (coumarins 1, 2, 6 and 8) have never been reported in the literature, i.e., these structures have been specifically designed to act as photoinitiators for silicones upon near UV and visible irradiation. Good final reactive epoxy function conversions (FCs) and also high rates of polymerization (Rp) were achieved in the presence of the newly proposed coumarin-based systems. The polymers generated from the photopolymerization of epoxysilicones can be considered as attractive candidates for several applications such as: elastomers, coatings, adhesives, and so on. The goal of this study focuses also on the comparison of the new proposed coumarins with well-established photosensitizers i.e., 1-chloro-4-propoxythioxanthone (CPTX), 9,10-dibutoxyanthracene (DBA) or some commercial coumarins (Com. Coum). As example of their high performance, the new proposed coumarins were also used for laser write experiments upon irradiation with a laser diode at 405 nm in order to develop new cationic 3D printing systems.